Respuesta :
First factor out the 2:
x^2 - y^2 = 36
x^2 - y^2 can be factored into (x+y)(y-y) so:
(x + y)(x - y) = 36
plug in your value:
18 (x-y) = 36 and you should be able to take it from there
x^2 - y^2 = 36
x^2 - y^2 can be factored into (x+y)(y-y) so:
(x + y)(x - y) = 36
plug in your value:
18 (x-y) = 36 and you should be able to take it from there
2x^2-2y^2=72
divide both sides by 2
x^2-y^2=36
factor difference of 2 perfect squares
(x-y)(x+y)=36
given that x+y=18, subsitute 18 for x+y
(x-y)(18)=36
divide both sides by 18
x-y=2
divide both sides by 2
x^2-y^2=36
factor difference of 2 perfect squares
(x-y)(x+y)=36
given that x+y=18, subsitute 18 for x+y
(x-y)(18)=36
divide both sides by 18
x-y=2